Pathologists’ Perceptions Regarding Oropharyngeal Specimens during Covid-19 Pandemic : Pathologists and COVID-19 - Sheikh, Mahrukh; Zaheer, Marium; zafar, Syeda Sadia; Shamim, Saba Hassan; Urooj, Arsala; Avesi, Lubna; Avesi, Lubna (Pakistan Journal of Medicine and Dentistry, 2024)
Background: The Covid-19 pandemic effected individuals worldwide. A significant number of specimens examined by pathologists are obtained from oropharyngeal region containing a highly viral titer along with increased preference of the virus to these tissues compared to other areas of the body requiring. The need of knowledge, attitudes such as appropriate Personal Protective Equipment (PPE) along with discarding of samples and adherence to protocols while dealing with these samples is necessary. Therefore, we aimed to assess the knowledge, attitude and practices of oral pathologists pertaining to modifications in laboratory protocols issued by various international organizations.Methods: A validated questionnaire with 22 close-ended questions was given to academic faculty, practicing pathologists and trainees of the pathology department working in a government institute (n=37). Statistics were applied and p